The first synapse in vision in the aging mouse retina - Gierke, Kaspar; Lux, Uwe Thorsten; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (Frontiers in Cellular Neuroscience, 2023)
Vision is our primary sense, and maintaining it throughout our lifespan is crucial for our well-being. However, the retina, which initiates vision, suffers from an age-related, irreversible functional decline. What causes this functional decline, and how it might be treated, is still unclear. Synapses are the functional hub for signal transmission between neurons, and studies have shown that aging is widely associated with synaptic dysfunction. In this study, we examined the first synapse of the visual systemthe rod and cone photoreceptor ribbon synapsein the mouse retina using light and electron microscopy at 2-3 months, ~ 1 year and > 2 years of age. We asked, whether age-related changes in key synaptic components might be a driver of synaptic dysfunction and ultimately agerelated functional decline during normal aging. We found sprouting of horizontal and bipolar cells, formation of ectopic photoreceptor ribbon synapses, and a decrease in the number of rod photoreceptors and photoreceptor ribbon synapses in the aged retina. However, the majority of the photoreceptors did not show obvious changes in the structural components and protein composition of their ribbon synapses. Noteworthy is the increase in mitochondrial size in rod photoreceptor terminals in the aged retina.